Beyond the Partnership Paradigm: Toward an Extended Typology of Government/Nonprofit Relationship Patterns. (April 2023) - Toepler, Stefan; Zimmer, Annette; Levy, Katja; Fröhlich, Christian
This article takes a fresh look at nonprofit/government relations in the context of both the partnership literature on collaboration and the closing space literature on repression. Following the Weberian ideal-type approach, we develop a heuristic tool for nuanced analyses of relations between the sectors in comparative research that is applicable in diverse political regime settings. We integrate foundational conceptions of Salamon, Young, and Najam to develop our framework, which we then illustrate with the cases of Russia and China. While repression is not necessarily the predominant characteristic of nonprofit–government relations in authoritarian regime settings, the reduction of intersectoral relations to collaboration strategies common in Western contexts also falls short of capturing the full complexity of the relationship. Rather than trying to establish national patterns, researchers need to remain sensitive to the coexistence of multiple government/nonprofit relationship types, affecting various parts of the nonprofit sector differently.